ANALYSIS OF COMPRESSIVE STRENGTH OF CONCRETE BY USING SLAG CIRCUM AS A CONCRETE AGGREGATE MIX - YONAS PRIMA ARGA RUMBYARSO (CV KULTURA DIGITAL MEDIA, 2022)
Currently, a lot of research has been carried out on the utilization of manufacturing industry products, one of which is steel slag as a mixed material for construction and the agricultural industry. One of the uses of steel slag in the construction sector is the manufacture of cement slag, as a mortar mixture, or as a mixture of sub-base layers for road pavement construction. The purpose of this study was to analyze the compressive strength of normal concrete compared to concrete added with slag circum waste as a partial replacement for fine aggregate with variations in the addition of 10% and 20% waste . This study uses an experimental method of planning normal concrete fc' 20 and concrete fc' 20 with variations of 10% and 20% slag circum as a substitute for fine aggregate by comparing the results of the compressive strength of concrete at 7, 14, and 28 days. In this study, it was found that the compressive strength of normal concrete without the addition of circum slag at the age of 7, 14, and 28 days was still better than the compressive strength of concrete at the age of 7, 14, and 28 days with the addition of 10% circum slag, and 20%. .